Perlindungan Hukum Pemegang Lisensi Hak Cipta Menurut Undang-Undang Nomor 28 Tahun 2014 Tentang Hak Cipta - Aulia Munadiah; Syafrudin Makmur; Tresia Elda (JOURNAL of LEGAL RESEARCH, 2021)
The main problem in this thesis is the rampant violations of cinematographic works by several parties illegally, such as what happened in the case in Decision Number 14/Pdt.Sus.Hki/Cipta / 2018 / Pn-Niaga Sby which could harm a license holder of the work.. The purpose of this study was to determine the legal protection of copyright license holders from copyright infringement and to find out the basic analysis of the judges' considerations and decisions in the dispute of Decision Number 14 / Pdt.Sus.Hki/Cipta/2018/Pn-Niaga Sby. This research method uses a normative juridical approach. The juridical normative in this study has two sources of law, namely primary and secondary sources of law. The primary source of law refers to Act No. 28/2014, on the Copyright. The theory used in this research is the theory of legal protection and the theory of intellectual property rights. The results of this study indicate that the regulation regarding legal protection has been regulated in Act No. 28/2014, on the Copyright, the problems in the judge's decision in decision Number 14/Pdt.Sus.Hki/Cipta / 2018 / Pn-Niaga Sby, the panel of judges rejecting the defendant's exception and granting the Plaintiff's Lawsuit. Some forms of evidence used in this case are a license agreement for the work which is the object of violation.Keywords: Legal Protection, Infringement, Copyright, License Holder.